The Role of the Dinas Sosial in Handling Beggars at Makassar City - Nur Aprilyanti; Muh Nur Yamin; Andi Cudai Nur (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
This study aims to determine the role of the Dinas Sosial in Handling Beggars at Makassar City and the factors that influence the rise of beggars at Makassar City. This type of research is descriptive research with a qualitative approach. The data collection techniques were carried out by observation, interviews and documentation. The results of this study indicate that the role of the Dinas Sosial in handling beggars at Makassar City is less effective, this can be seen from the three role indicators according to Gede Diva, namely the government has not acted as a facilitator, has not acted as a regulator and has acted as a catalyst. Based on the results of the study, two of the three indicators have not played a maximum role in handling beggars. This is due to the unavailability of facilities in the form of advanced rehabilitation homes for beggars to receive guidance and the lack of skills training provided by the Dinas Sosial of Makassar City to beggars. The internal factors of the rise of beggars at Makassar City are migrating with desperate capital, lazy to do business, and physical disabilities while the external factors are the absence of jobs, expensive prices of basic necessities, poverty and acute economic problems.